Two Deaths Based on the Novel "The Two Deaths of Senora Puccini" by Stephen Dobyns - Roeg, Nicholas; Stok, Witold; Gambon, Michael; Braga, Sonia; Malahide, Patrick (Tartan Video, 1997)
Two Deaths (1995), an oppressive, talky chamber piece about romantic obsession, set in Bucharest as the Ceausescu government falls ... [www.screenonline.org.uk]